Pengembangan Hutan Sagu Menjadi Kebun Sagu Dusun Kampung Baru Negeri Dawang Kabupaten Seram Bagian Timur - Riry, Roberth Berthy (Universitas Pattimura, 2023)
Sago forests are a natural resource with significant potential for economic development and meeting the food needs of local communities. However, in recent decades, sago forests have faced degradation due to illegal logging and unsustainable agricultural practices. Transforming sago forests into sago plantations is a sustainable solution to maintain ecosystem balance and improve community welfare. In East Seram Regency, sago forests cover an area of 36,075 hectares, spread across several districts. This initiative aims to harness the potential of transforming sago forests into sago plantations while accelerating the sago harvesting cycle. The methods used include field surveys, interviews with stakeholders and local communities, and spatial data analysis. The findings show that sufficient sago land is available, but challenges remain: accessibility is difficult, processing equipment is still rudimentary, the organization of the main plantation area is unstructured, and key infrastructure, such as Sagu Molat seedling nurseries, farm shelters (guard houses), and processing houses, is either very limited or non-existent.